1999
DOI: 10.1038/sj.ijo.0800767
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and heritability of BMI in Finnish adolescents aged 16 y and 17 y: A study of 4884 twins and 2509 singletons

Abstract: OBJECTIVE: 1) To estimate the heritability of body mass index (BMI) in twins aged 16 y and 17 y, with a special emphasis on gender-speci®c genetic effects and 2) to compare heights, weights, BMIs, and prevalences of`overweight' (BMI ! ! 25 kgam 2 ) in these twins and in singletons aged 16.5 y. DESIGN: Cross-sectional and longitudinal epidemiological questionnaire study of twins at ages 16 y and 17 y, and cross-sectional study of singletons at age 16.5 y. MEASUREMENTS: BMI (kgam 2 ) was calculated from self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
3
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 23 publications
(52 reference statements)
6
103
3
3
Order By: Relevance
“…A study in Finnish adolescent twins reported that 17-year-old twin boys had reached the same height as singletons but still had a lower BMI. 13 The same tendency, although not reaching significance, was seen in girls. They suggested that the catch-up growth from the lighter birth weight may not (yet) be completed in twin boys.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A study in Finnish adolescent twins reported that 17-year-old twin boys had reached the same height as singletons but still had a lower BMI. 13 The same tendency, although not reaching significance, was seen in girls. They suggested that the catch-up growth from the lighter birth weight may not (yet) be completed in twin boys.…”
Section: Discussionmentioning
confidence: 72%
“…10 Several studies have shown that the differences in body size between twins and singletons at birth disappeared during childhood, but in a few studies differences remained until adulthood. [11][12][13][14][15] The Louisville Twin Study concluded that the effects of prenatal growth suppression on weight and height appeared to be fully dissipated by age 8, 11 and a Finnish study among 17-year-old twins reported that twins were as tall as singletons, but that boy twins were still leaner. 13 We found in a previous study that at the age of 5 years, female twins were as tall as singleton children, whereas male twins were still somewhat shorter than children in the general population.…”
mentioning
confidence: 99%
“…These results are based on the meta-analysis of the nine existing twin studies. [13][14][15][16][17][18][19][20][21] Background information of these cohorts is presented in Appendix Table A1 and the estimates of variance components with 95% CI for each study in Appendix Table A2.…”
Section: Resultsmentioning
confidence: 99%
“…In the case when studies reporting correlations in BMI have been presented several times in different papers, only one paper was included. On the basis of these criteria, we found nine twin studies [13][14][15][16][17][18][19][20][21] and five adoption studies; [22][23][24][25][26] however, no family studies reporting heritability estimates of childhood obesity were found. In addition, we found three twin studies that had pooled information on children at different ages.…”
mentioning
confidence: 99%
“…These results suggest protein and energy intakes and school physical education activity might also contribute to BMI, though that BMI is mainly genetically determined (Pietilainen et al, 1999). Socioeconomic area was another environmental factor associated with BMI (Table 1), probably reflecting the uneven rate of development in different areas of China in recent years.…”
Section: Discussionmentioning
confidence: 92%